CHARACTERISTICS AND RISK FACTORS OF PATIENTS WITH NASOPHARYNGEAL CARCINOMA IN WEST NUSA TENGGARA HOSPITAL - Mochammad Alfian Sulaksana; Hamsu Kadriyan (TALENTA PUBLISHER, 2019)
Introduction Nasopharyngeal carcinoma (NPC) is the most common cancer in the head and neck. NPC is a malignancy of squamous cell on nasopharyngeal epithelial with the most common predilection site in rosenmuller fossa. Theetiology of this disease are multifactorial. A low oral hygiene on naso-oro-hypopharyngeal/laryngeal wall, Epstein Barr Virus (EBV) infection, smoking, alcohol consumption, genetic/hereditary factors, exposure to radiation, nutritional, deficiencies or decreased imune system are recognized as a risk factors. The study aim is to find out a characteristic of patients with nasopharyngeal carcinoma and their risk factors in the west Nusa Tenggara Hospital in September-October 2018. Methods The study design was descriptive–cross sectional. The research subjects were NPC patients who came to the West Nusa Tenggara Hospital ENT-HNS Clinic, in the period September-October 2018. Results There were 37 patients enroled to this study. According to this study, the most patients found in age group 46 to 55 years (35.1%), predominantly men (67.6%) with the men and women ratio 2.5: 1. Based on patients origin, they come from all districts in west Nusa Tenggara province, with the most districts found in West Lombok (29.7%). The most risk factors were food factors (food preservative 19.9%, food flavoring 19.9%, salted fish 15.6% carcinogenic (grilled food) 6.5%), and environmental factors (cigarettes 11.3%, smoke 4.8 % and 4.8% dust). Conculsion There were several risk factors found in this study, however, the most risk factor was food factors (61.9%) followed by environmental factors (20.9%).